Haciendo viable la minería peruana: el caso de minería Gold Land - Centeno Rojas, Adolfo (2007)
Although mining is at present a signifi cant source of foreign currency fl ows to Peru, it went through times of crisis when metal quotations dropped. Many international mining majors weathered the crises with the fi nancial backing of their parent companies or fi nancial multilaterals, and their operative economies of scale. In the wake of the crisis, some small and intermediate mining companies closed their operations, leaving behind a negative impact of their communities and a degraded environment. Yet, other companies, thanks to the commitment of their shareholders, workers and local banks, introduced a number of initiatives to negotiate the crisis. The story of Gold Land Mining illustrates the case of those companies that managed to survive during very dire times.